Effect of twine thickness on size selectivity and catch efficiency of gillnets used in Prussian carp (Carassius gibelio) fisheries - Atessahin, Tuncay; Cilbiz, Mehmet; IIhan, Mahmut (Ege Univ, Fac Fisheries, 2026)
This study evaluated the effects of twine thickness and mesh size on the size selectivity and catch efficiency of gillnets used to control the invasive Prussian carp, Carassius gibelio (Bloch, 1782) population in the Karakaya Dam Lake, Tü rkiye. A total of 1.675 individuals ranging from 17.0 to 31.2 cm in length were captured. Among the tested configurations, the gillnet with 84 mm mesh size and 0.23 mm twine thickness demonstrated the highest catch efficiency, accounting for 50.4% of the total catch, whereas the 76 mm mesh with 0.18 mm twine yielded only 17.9%. Statistical analysis confirmed that mesh size significantly influenced the average length of captured fish (p < 0.05), with larger mesh sizes capturing longer individuals. Seasonal variation was notable, with peak catches observed in December (375 specimens) and January (316 specimens), aligning with the winter schooling behaviour of the species that enhances catchability. The SELECT method was used to model size selectivity, and the lognormal model provided the best fit across all twine thicknesses. Modal lengths of 20.59 cm (0.23 mm), 20.97 cm (0.20 mm), and 21.64 cm (0.18 mm) were estimated, indicating minimal variation due to twine thickness. Although twine thickness did not significantly affect selectivity, it enhanced catch efficiency, particularly for larger individuals. These findings suggest that gillnets with thicker twine and larger mesh sizes are more effective for managing C. gibelio populations, especially during winter months. Moreover, the use of durable gear contributes to reduced gear loss and increased operational lifespan, supporting the socioeconomic sustainability of local fisheries. This research provides a scientific foundation for developing seasonally optimized and gear-specific strategies for managing invasive species in Turkish inland waters.
Keywords: Invasive species management; catch efficiency; gillnet selectivity; twine thickness